Effect of Professional Commitment, Ethical Environment and Personal Cost on Intention to do Whistleblowing - Khairunnisa, Khairunnisa; Hizazi, Achmad; Tiswiyanti, Wiwik (Journal of Business Management and Economic Development, 2023)
This research was conducted to find out what factors influence a person's intention to do whistleblowing. The purpose of this study is to find out whether professional commitment, ethical environment, and personal costs affect the intention to do whistleblowing at the Public Works and Public Housing Office of Jambi Province. This study uses primary data and was obtained through questionnaires distributed to Civil Servants  who work at the Public Works and Public Housing Office of Jambi Province with a research sample of 71 respondents who work at the agency with the sampling technique using simple random sampling. The data analysis method used in this research is multiple linear regression analysis using the SPSS 25 program. The results of this study indicate that professional commitment, ethical environment, and personal costs have an influence on the intention to do whistleblowing. So it can be concluded that the higher the individual's professional commitment, the higher the intention to do whistleblowing, the higher the understanding of ethics in a work environment, the higher the intention to do whistleblowing, and the higher the personal cost, the higher the intention to do whistleblowing.